Penerapan Metode Fuzzy Weighted Product untuk Mengukur Tingkat Kemiskinan di Wilayah Provinsi Sumatra Barat - Sawitri, Sawitri; Alisah, Evawati (Jurnal Riset Mahasiswa Matematika, 2024)
The Fuzzy Multi-Attribute Decision Making (FMADM) method is an approach to find the best choice from a number of alternatives according to predetermined criteria. In FMADM, there is a technique called Fuzzy Weighted Product (FWP), which uses the concept of ranking by multiplying the value of the criterion by its weight. The weight of the criterion is calculated by multiplying the value by the weight of the criterion. This study aims to apply FWP in assessing the poverty level in an area, where poverty reflects the unmet economic needs of the community according to the average standard of living of the region. One proposed solution is to use the FWP method. This process begins by setting goals, alternative decisions, and criteria that will be used to determine poor areas in West Sumatra Province. The steps to implement FWP include the determination of criteria and their weights, the assessment of alternative preferences (S), and the evaluation of relative preferences (V). The best decision is determined based on the highest relative preference value, which is expected to support decision making in poverty-stricken districts in West Sumatra Province.